Effects of Anterior Plating on Clinical Outcomes of Anterior Lumbar Interbody Fusion. Issue 7 (August 2016) - Snyder, Laura A.; Kalb, Samuel; Kakarla, Udaya K.; Porter, Randall W.; Kaibara, Taro; Dickman, Curtis A.; Theodore, Nicholas
Abstract : Study Design: Retrospective review. Objective: To compare surgical outcomes of patients who have undergone anterior lumbar interbody fusion (ALIF) with and without plating. Summary of Background Data: In biomechanical testing, ALIF constructs supplemented with plating (ALIFP) reduce range of motion and increase construct stiffness compared with ALIF alone. However, whether ALIFP constructs translate into improved clinical outcomes over ALIF alone is unknown. Methods: From 2004 through 2010, 231 patients underwent ALIF with (146) or without (85) plating. Eight patients lost to follow up were excluded from final evaluation. Patients' records were evaluated retrospectively for demographics, complications, and outcomes. Results: At a mean follow-up of 13.7 months (range, 1–108 mo), the mean Economic, Functional, and Total Prolo scores for ALIF patients were 4.23, 3.63, and 7.87, respectively. The mean Oswestry Disability Index (ODI) was 24%. At a mean follow-up of 11.2 months (range, 1–93 mo), the mean Economic, Functional, and Total Prolo scores for ALIFP patients were 4.28, 3.67, and 7.95, respectively. The mean ODI was 22.9%. There was no significant difference between rate of complications or Prolo scores or ODI between the 2 groups ( t test). Neither diabetes, hypertension, smoking, sex, nor age older than 55 years was significantly related to whether patients had higher Prolo scores with or without plating. Patients with a normal body mass index and ALIF had significantly better Prolo Economic scores and total scores than patients with a normal body mass index and ALIFP ( P =0.04 and 0.02, independent samples t test). Patients were also stratified by surgical indication for surgery, and there was no significant difference in Prolo scores or ODI for patients who underwent ALIF alone versus ALIFP. Conclusions: Even when stratified by indication for surgery, anterior plating does not seem to improve Prolo scores or ODI, suggesting that not all patients undergoing ALIF require plating.